2022
DOI: 10.1021/acsenergylett.2c00359
|View full text |Cite
|
Sign up to set email alerts
|

Dispersing Agents Impact Performance of Protonated Phosphonic Acid High-Temperature Polymer Electrolyte Membrane Fuel Cells

Abstract: The microstructure of ionomers plays a significant role in the performance of high-temperature polymer electrolyte membrane fuel cells (HT-PEMFCs). Here, we establish direct correlations between the properties of dispersing agents and the microstructure of a protonated phosphonic acid ionomer. Most importantly, the formation of the porous structure of a protonated phosphonic acid ionomer depends on the pK a of the liquid media. Namely, the acid−base interaction between the charged polymer and dispersing agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The dried electrodes were assembled with the PA-doped HTMA-DAPP membrane and PTFE gaskets. The detailed MEA fabrication process was described in a previous report …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dried electrodes were assembled with the PA-doped HTMA-DAPP membrane and PTFE gaskets. The detailed MEA fabrication process was described in a previous report …”
Section: Methodsmentioning
confidence: 99%
“…The detailed MEA fabrication process was described in a previous report. 39 HT-PEMFC performance was tested using the two MEAs. The MEAs were preconditioned under a stepwise change of voltage from 0.7 to 0.4 V overnight, followed by running the cell with H 2 /O 2 flow under a water vapor pressure of 46.7 kPa for 3 h at a constant current density of 0.2 A cm 2 .…”
Section: H Nmr Figures S5−s8)mentioning
confidence: 99%
“…In particular, phosphonated poly­(pentafluorostyrene) exhibited stable proton conductivity even at 200 °C. However, ameliorating gas diffusion through binders, especially oxygen accessibility, is still a major challenge in HT-PEMFCs . Recently, great efforts have been devoted to promoting gas permeation in ionomers.…”
Section: Introductionmentioning
confidence: 99%
“…Modestino et al reported that the amorphous domain with a high fractional free volume (FFV) in PFSA ionomers reduced the resistance for gas permeation significantly. Kim and co-workers , investigated the dispersing-agent-induced phase separation to fabricate the porous structure in phosphonated poly­(pentafluorostyrene) ionomers. Wang et al presented a composite ionomer by introducing a sulfonated covalent organic framework (COF) into Nafion to promote oxygen permeation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation